Synthesis and Characterization of PLA/Luffa Cylindrica Composite Films - Krishnudu, D. Mohana; Dowluru, Sreeramulu; P, Venkateshwar Reddy (International Journal of Integrated Engineering, 2020)
In recent days, natural fibers have been replaced with synthetic fibers as an alternative material for the reinforcement in the polymer composites due to their renewability and sustainability. The aim of the present work is to study the performance of using natural fiber powder in the preparation of composite films. The fiber powder used in the present study is extracted from the Luffa cylindrica plant. Fourier Transform Infrared (FTIR) spectrum is utilized for the identification of functional groups in the fabricated composite film. Scanning Electron Microscopy (SEM) analysis is carried out to observe the bonding between matrix and reinforcement in the composite films. Thermal degradation behaviour of the composite film is also studied by the Thermo-gravimetric Analysis (TGA). From the studies, it was observed that the natural fiber reinforced composite film were able to withstand higher temperatures. The fabricated composites films can be effectively used for different applications where there is a necessity of bio polymers.